A documentary study of the felt effects of the great California earthquake of 1857 - Sieh, Kerry (2013)
We have collected over 60 hitherto unpublished accounts of the California earthquake of January 9, 1857. We have used them, together with those already known, to estimate felt intensities and prepare an isoseismal map which roughly indicates the level of short-period ground motion experienced during this earthquake. Modified Mercalli intensities of VI to VII occurred in the modern metropolitan areas of southern California, and VI to VIII in the southern San Joaquin Valley. The intensity along the fault was IX or more. Instances of seiching, fissuring, sandblows, and hydrologic changes were reported from Sacramento to the Colorado River delta. Most reports say that shaking lasted between one and three minutes. At least two large aftershocks occurred within a week of the main event.